CYBER RESILIENCE: GLOBAL THREATS AND NATIONAL CYBER DEFENSE STRATEGIES - Rybalchenko, L. V.; Haborets, O. A.; Prokopovych-Tkachenko, D. I. (Systems and Technologies, 2024)
The widespread use of information technologies leads to numerous crimes and the emergence of new types of threats based on the use of various means, methods and elements of influence on human consciousness. The formation of a single global information space has enabled everyone to access information from different parts of the world. Remote management of business, management of personal assets, conducting transactions, provides criminals with new means of interfering with personal data of citizens in order to obtain them. The purpose of the article is to study the global information space, which has become a limitless place and tool for crime. Information and communication systems have become the main instrument of crime. The use of illegal technical means, creation of viruses, spam, phishing attacks and other means have enabled cybercriminals to gain access to confidential information, databases, restricted information, payment cards, bank accounts and automated management systems in order to steal and take possession of data, resulting in various forms of fraud. The theft of personal data and commercial information to seize the funds of bank customers, deliberate damage and corruption of information systems and communications is a small list of malicious actions of modern fraudsters that cause losses to enterprises, institutions, organizations and individuals. The use of various attacks on Internet resources with the help of rapidly developing modern information technologies has become the basis for cybercriminals to cause damage and losses to the country’s critical infrastructure. It has been established that in times of war, the number of cybercrimes has increased many times and is being committed to destabilize the state, cause damage, disable equipment, technology, communications and communications. Hacker attacks can gain control over personal data, databases of large enterprises and institutions, and become a threat to data leakage and network damage.